The Role of the United Nations and Its Agencies in the Israel-Hamas War - Mbah, Ruth Endam; Mbah, Drusilla Engonwei; Hultquist, Laura (Advances in Social Sciences Research Journal, 2024)
Institutional Liberalism, an International Relations theory argues that international institutions play a significant role in influencing cooperation and peace among nations. Although criticized by some as unrealistic, the tenets of Liberal Institutionalism have contributed to the rising interest in the capabilities of international organizations like the United Nations (UN) in ensuring long-lasting international relations and peace among countries after the Cold War Era. This is due to their mediation ability that provides a ‘common ground’ for discussions among states while maintaining the common interest of each state actor. It is considering this tenet of Institutional Liberalism that we explore the role of the UN and some of its agencies in the ongoing Israel-Hamas war of 2023. The involvement of the UN in the Israeli-Palestinian tension dates back to November 29, 1947, when the UN General Assembly voted to divide Palestine into Jewish and Arab states with Jerusalem as its international city (Resolution 181- Partition Plan). However, the focus of this article is limited to the October 7, 2023, Israel-Hamas war, as the role of the UN and its agencies have been active in mediating international relations in a manner supported by the theory of Liberal Institutionalism. The agencies under consideration in this article include the UN General Assembly, UN Security Council, International Court of Justice, UNHCR, UNRWA, UNESCO, UNICEF, and WFP. This article is, however, limited to a few UN agencies and, as such, gives room for further research as to the role of unexamined UN agencies as well as other international institutions in the ongoing 2023 Israel-Hamas war.